GAMBARAN ACADEMIC BURNOUT PADA MAHASISWA KEPERAWATAN - Akladiwa .S. Magribi; Jumaini Jumaini; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Academic burnout is a condition in which a person experiences physical, emotional, and mental exhaustion caused by demanding academic situations over a long period of time. Students majoring in nursing can be at risk of academic burnout since their routines life and tasks are encountered in the study. This study aims to determine the description of academic burnout in nursing students. This research was descriptive method with cross sectional approach. The sample used in this study was 250 nursing students with total sampling technique. The research instrument used Maslach Burnout Inventory-Student Survey (MBI-SS). Data analysis used univariate analysis with distribution and percentage. The result of the univariat test showed that the most of the respondents are 20 years old (46.0%), the majority are female (89.6%) and most of the respondents experienced academic burnout in the moderate category (61.2%). Researchers expect nursing students to be able to manage their time effectively, manage work overload in carrying out routines without too much pressure and manage stress well (coping stress) to avoid academic burnout.Keywords: Academic burnout; exhaustion; nursing student